Effect of arbuscular mycorrhizal fungi and ovine manure on the initial growth of papaya (Carica papaya L.) 'Maradol roja' (Bioagro, 2020)
The inoculation of arbuscular mycorrhizal fungi (AMF) and the use of manure are sustainable practices with minim impact on the ecosystem that can improve the growth and nutrition of plants. The objective of this work was to evaluate the effect of AMF and ovine manure on the initial growth of papaya plants (Carica papaya L.) var. Maradol Roja. Five treatments were evaluated: plants cultivated in sand inoculated with Scutellospora fulgida (SF), Funneliformis mosseae (FM) and Glomus manihotis (GM), and two controls, a commercial substrate (sand with ovine manure, E), and sand alone. The AMF or the manure were mixed with the sand in a 1:2 volumetric proportion. A completely randomized experimental design was used with twenty repetitions. At day 60 after the inoculation the following variables were measured: percentage of colonization by AMF (PCA), plant height (PH), number of leaves and nodes, radical system length, stem diameter, dry biomass of aerial part, leaf area (LA), LA index (LAI), and contents of chlorophyll a (Ca), b (Cb), both chlorophylls (Cab), and carotenoids (Cc). The analysis detected significant differences (P≤0.05) for PCA, LA, LAI, PH, Ca, Cb, Cab y Cc by effect of the applied treatments. It was concluded that the AMF (SF, MF and GM) and E influenced the initial growth and contents of chlorophylls and carotenoids in the papaya plants, and obtained the highest Ca. The plants on substrates with ovine manure reached the maximum Cab, Cb and Cc.
Keywords: AMF; Funneliformis mosseae; Glomus manihotis; Scutellospora fulgida